Education as Ascetic Practice: Teaching Theology in a Post-9/11 Context - O'Brien, Maureen R. (Horizons, 2004)
This essay presents an argument for the inherently ascetic nature of education in theology when considered in the wake of the September 11, 2001, terrorist attacks on the United States. Using a specific undergraduate theology course on Christian and Muslim responses to war and violence as a test case, the essay describes ascetic education as creating an epistemological "space" in which the capacity to engage complexity is intentionally enlarged and transformed. This enlargement, in the course under discussion, occurred principally through the students' encounter with diverse historical Christian responses to the question of participation in war, along with the comparison of Western and Muslim notions of "just war" as differentiated by historical, political and cultural factors. After presenting some highlights of how course themes and methods engaged the central ascetic tensions in the post-9/11 situation, three dimensions of asceticism vis-à-vis education are presented: ascetic disposition, conversation and action.